2018
DOI: 10.1080/20426445.2018.1475918
|View full text |Cite
|
Sign up to set email alerts
|

Polyesterification of wood using sorbitol and citric acid under aqueous conditions

Abstract: The aim of this research is to determine if the polyesterification of sorbitol and citric acid in wood has a future potential as a wood modification process. Pine wood was impregnated with an aqueous solution containing citric acid and sorbitol and was thereafter cured at 103 or 140°C for 18 hours. The dimensional stability and leaching resistance were studied for both modification temperatures. The leachates from the modified wood samples were analysed by HPLC and the susceptibility to decay and staining fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 26 publications
4
39
2
Order By: Relevance
“…Larnøy et al [52] found the treated pine sapwood samples cured at 140 • C are more stable to that of cured at 103 • C as no leachate was detected in the former by HPLC analysis. It is implied that curing temperature of 103 • C is not sufficient to ensure complete reaction between CA and sorbitol.…”
Section: Curing Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…Larnøy et al [52] found the treated pine sapwood samples cured at 140 • C are more stable to that of cured at 103 • C as no leachate was detected in the former by HPLC analysis. It is implied that curing temperature of 103 • C is not sufficient to ensure complete reaction between CA and sorbitol.…”
Section: Curing Temperaturementioning
confidence: 99%
“…European beech (Fagus sylvatica) sapwood modified with CA and sorbitol solution at different concentrations has shown an increment in density, pH, and thickness swelling (TS), where the increment increased along with increasing CA-sorbitol concentrations [19]. Larnøy et al [52] treated Scots pine sapwood (Pinus sylvestris) with a combination of sorbitol and CA and some selected properties of the treated wood were assessed. As a result of the treatment, resistance against brown rot, white rot, and blue stain fungi of the treated pine sapwood were improved significantly.…”
Section: Citric Acid With Sorbitolmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies on the utilization of sorbitol for wood modification have been limited to describing solely the dimensional stabilization of the wood matrix [19]. In recent studies, SCA-modified wood was shown to exhibit not only enhanced dimensional stability, but also durability against decay fungi and reduced susceptibility to blue stain fungi [20].…”
Section: Introductionmentioning
confidence: 99%
“…Polyesterification of bio-based chemicals in wood as an impregnation chemical modification technique is a field which has been gaining research attention over the past decade [5][6][7][8][9][10][11][12][13]. One promising method utilising relatively low-cost chemicals is polyesterification using sorbitol and citric acid (SCA) [14,15]. The uncatalyzed reaction of citric acid with alcohols or polyols is thought to proceed through a cyclic anhydride intermediate formed by dehydration of the citric acid ( Figure 1a,b) which then reacts with a hydroxyl group in the alcohol/polyol (Figure 1c) to form an ester ( Figure 1d) [16].…”
Section: Introductionmentioning
confidence: 99%